PERBANDINGAN TINGKAT KOMPARATIF DAN SUPERLATIF ADJEKTIVA DALAM BAHASA INGGRIS DAN BAHASA INDONESIA (KAJIAN LINGUISTIK KONTRASTIF) - Beina Prafantya (Jurnal Sosioteknologi, 2011)
The title of this paper is "Comparative and Superlative Comparison of Adjectives in English and Indonesian Language (An Analysis of Contrastive Linguistics)". This paper contained of problems about the degree of comparison of adjectives in English as the most popular foreign language used in Indonesia and Indonesian Language itself. Problems analyzed in this paper is the morphological process of the adjectives which shows the degree of comparative and superlative in English and Indonesian language. It is also discussed the difference of the morphological process in degree of comparison of adjectives: comparative and superlative in English and Indonesian language. The result shows that in English, the morphological process used to build the comparative and superlative adjective is defined by the number of the syllables and the last sound of the words in the words contained by two syllables. In Indonesian language, the comparative and superlative adjective is defined by the adverbial phrase followed by the adjectives. Key Words: Comparative, Superlative, Adjective, Syllable, Adverbial Phrase